La configuration des échanges dans un modèle à biens multiples : quelques paradoxes - Casas, F. (L'Actualité économique)

(untitled) (HEC Montréal, 1978)
In the framework of a two-good, two-factor model it is evident that the pattern of trade can be inferred from the change in commodity prices resulting from the opening of trade. Thus, if trade increases the relative price of a commodity, we expect that commodity to be exported, while the good whose relative price decreases will be imported.Under certain circumstances however, it may be possible to observe a country importing a commodity even though its free trade relative price is higher than under autarky.The purpose of this paper is to point out that a similar paradox can be established even if we rule out distributional effects of changes in commodity prices on the demand for goods attributable to different tastes. In particular, we focus our attention on a simple three-good, two-factor model with fixed production coefficients. It is well known that when the number of goods exceeds the numbers of factors, a basic indeterminacy exists in the relationship between output levels and relative commodity prices. Our interest lies in establishing that one application of this indeterminacy is that technological characteristics—in particular, the factor intensity ranking of commodities and a country's factor endowment—may result in the reversal of the expected pattern of trade.